Environmentally benign silver bio-nanomaterials as potent antioxidant, antibacterial, and antidiabetic agents: Green synthesis using Salacia oblonga root extract - Dugganaboyana, Guru Kumar; Kumar Mukunda, Chethan; Jain, Anisha; Kantharaju, Raghavendra Mandya; Nithya, Rani R.; Ninganna, Divya; Ahalliya, Rathi Muthaiyan; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I.; Silina, Ekaterina; Stupin, Victor; et al. (Frontiers in Chemistry, 2023)
Silver nanoparticles (AgNPs) were synthesized employing a high-efficiency, non-toxic, cost-effective green and simple technique that included the use of Salacia oblonga root extract (SOR) as a capping agent compared to synthetic nanoparticles. The usage of S. oblonga can be seen in traditional medicines for treating diabetes, obesity, rheumatism, gonorrhea, asthma and hyperglycemia. The objectives of the current study were to green synthesize S. oblonga root extract silver nanoparticles (SOR-AgNPs), characterize them and study their antioxidant, antibacterial, and antidiabetic activities. The shape of SOR-AgNPs was spherical with less than 99.8 nm in size and exhibited a crystalline peak at XRD. The green synthesized SOR-AgNPs showed significant antioxidant properties like DPPH (80.64 µg/mL), reducing power capacity (81.09±SEM µg/mL), nitric oxide (96.58 µg/mL) and hydroxyl (58.38 µg/mL) radical scavenging activities. The MIC of SOR-AgNPs was lower in gram-positive bacteria. The SOR-AgNPs have displayed efficient inhibitory activity against α-amylase, with an EC50 of 58.38 µg/mL. Analysis of capping protein around the SOR-AgNPs shown to have a molecular weight of 30kDa. Bio-fabricated AgNPs had a significant impact on bacterial strains and could be used as a starting point for future antibacterial drug development.